El «Teatre Estudi» de Lo Rat-Penat - Felipe Martínez, María Ángeles; Requena Pineda, Susana; Lacoba Vila, José Manuel (Caplletra. Revista Internacional de Filologia, 2015)
The authors have researched the renovating activities of the Teatre Estudi, nucleus of Lo Rat-Penat society, in which they distinguish two periods: the first, 1956-1957, under the presidency of Josep Alarte, and the second, 1958-1960, presided by Rafael Llorenç i Romaní. They offer a detailed follow-up of the plays performed for the first time, the mise-en-scène and the repercussion on audience attendance.